Firm Formation and Agglomeration under Monopolistic Competition - Stephan Brunow; Peter Nijkamp (Tinbergen Institute, 2013)
In the presence of agglomeration economies one might expect a relocation and concentration of industries. Then firm start-up activities may be assumed to reveal those effects. We introduce an empirical testable model inspired by the New Economic Geography and human capital externalities literature. The novelty of this paper is that it derives a measure of agglomeration economies founded on microeconomic analysis based on households' and firms' maximization behavior, namely the real market potential. Besides agglomeration forces, dispersion and human capital effects can be separated and explicitly controlled for. The paper sheds new light on the general mechanisms of intra-industrial agglomeration forces because it explicitly considers the regional distribution of economic activities. It offers clear evidence for the empirical relevance of the New Economic Geography.
Keywords: L13; O41; R11; R3; 330; New Economic Geography; Agglomeration; Externalities; Firm Formation